Author Correction: Methodological synthesis of Bayesian phylodynamics, HIV-TRACE, and GEE: HIV-1 transmission epidemiology in a racially/ethnically diverse Southern U.S. context - Kayo Fujimoto (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.